2018
DOI: 10.18778/2299-8403.07.06
|View full text |Cite
|
Sign up to set email alerts
|

Gatunki inwazyjne w dolinie środkowej Warty

Abstract: Analizą objęto inwazyjne gatunki roślin w środkowym odcinku doliny Warty. Badania prowadzono metodą transektów. Stwierdzono 21 gatunków roślin inwazyjnych. Najliczniej notowano: przymiotno kanadyjskie Conyza canadensis, klon jesionolistny Acer negundo, uczep amerykański Bidens frondosa, nawłoć kanadyjską Solidago canadensis oraz moczarkę kanadyjską Elodea canadensis. Gatunki inwazyjne występowały w 12 typach siedlisk przyrodniczych. Najliczniej stwierdzano je w lasach łęgowych (związek Alno-Ulmion) i z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Other authors found Conyza canadensis, which was found in the presented study in both farming systems with rather low average abundance of 2 plants per m −2 (organic farming system) and less than 1 plant per m −2 (conventional farming system). This invasive plant species was found by other authors to be one of the most abundant invasive weed species in both agricultural and other ecosystems [43,44].…”
Section: Invasive Weed Speciesmentioning
confidence: 70%
“…Other authors found Conyza canadensis, which was found in the presented study in both farming systems with rather low average abundance of 2 plants per m −2 (organic farming system) and less than 1 plant per m −2 (conventional farming system). This invasive plant species was found by other authors to be one of the most abundant invasive weed species in both agricultural and other ecosystems [43,44].…”
Section: Invasive Weed Speciesmentioning
confidence: 70%
“…In studies on the object, patches with the participation of Echinocystislobata were recorded. In wet habitats with a feature similar to drainage ditches, the authors indicate the appearance of many alien species, e.g., Impatiens glandulifera, Ambrosia artemisiifolia, and Sosnowski's borscht (Heracleum sosnowskyi) (Chmielecki and Kucharski, 2018;Dajdok and Pawlaczyk, 2009;Jackowiak, 1999;Lenda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of the communities at the watercourse and the drainage ditches, Echinocystislobata, which is an invasive alien species, was found. Its occurrence outside the natural range may threaten some communities' species diversity (Chmielecki and Kucharski, 2018;Dajdok and Tokarska-Guzik B., 2009;Dajdok and Pawlaczyk, 2009;Dylewski and Maćkowiak, 2014;Lenda et al, 2019;Commission Table 4. Natural indexation of appearing species of plants according to the method Oświt (2000).…”
Section: Invasive Species In Drainage Ditchesmentioning
confidence: 99%